Pengelolaan Data Peserta Didik Berbasis Administrasi Perkantoran di TK DYAS Montessori School - Moh. Irwan Hadi (AS-SABIQUN, 2026)
Although student data management is an important component of school administration, studies that specifically discuss student data governance in early childhood education institutions from an office administration perspective remain limited. This study aims to describe and analyze office administration-based student data management at TK DYAS Montessori School, focusing on the processes of recording, storage, updating, utilization, obstacles, and improvement efforts. This study used a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the kindergarten principal, administrative staff, and classroom teachers as key informants. The data were analyzed through the stages of data reduction, data display, and conclusion drawing, while data validity was strengthened through source and technique triangulation. The results showed that student data management at TK DYAS Montessori School had been implemented through the stages of data collection, recording, storage, updating, and utilization for administrative services, school reporting, communication with parents, and fulfillment of institutional document requirements. However, obstacles were still found in the form of incomplete student documents, data updates that had not been carried out regularly, suboptimal integration of manual and digital archives, and the absence of fully standardized operational procedures. Improvement efforts were carried out through document completion, archive arrangement, the use of simple digital data recapitulation, strengthening internal coordination, and the need to prepare clearer administrative procedures. The conclusion of this study affirms that office administration plays a strategic role in improving the accuracy, accessibility, security, and accountability of student data management in early childhood education units. These findings imply the importance of strengthening a school administration system that is orderly, well documented, and adaptive to data governance needs in kindergarten institutions.